Relatoria das entrevistas e webinar para o levantamento de percepções de representantes da cadeia da pecuária sobre o desenvolvimento de recursos digitais inclusivos na implementação de boas práticas - Freixêdas, Valeria M.; Moraes, Fernanda C.; Costa, Ciniro; Suber, Marta; Dittmer, Kyle M. (2022)
The digitization of food systems is well underway. The digital ecosystem and its actors have increasing influence over how food is produced, what food people buy, and flows of information among farmers, supply chain actors and consumers. Efforts to transform food systems towards sustainability, including climate change resilience and mitigation, similarly rely on digital resources and offer the opportunity to scale up best practices rapidly at lost cost. Yet differences in digital participation among farmers risk exacerbating inequities, and top-down digital information can lack local relevance and disempower farmers, especially smallholders. In this context, the Agroecological Transitions Program’s (TRANSITIONS) Inclusive Digital Tools project (ATDT) supports the use of inclusive digital resources and citizen science to stimulate the beef cattle chain in Brazil to create, adapt and innovate production practices based on agroecological principles. This report presents results of a stakeholder consultation carried out in October and November 2022 with the objective of understanding key areas, principles and priority actions to guide the development of inclusive digital resources for smallholder cattle ranchers in Brazil.